(untitled) (Scientific journal of the Fergana State University, 2024)
A large part of the territory of Syrdarya region is occupied by saline lands. In order to ensure the production of agricultural products in the region, reclamation works are being carried out in these areas. In this article, the economic efficiency of reclamation measures for desalination of saline lands was evaluated on the example of a conventional farm in the Syrdarya region of the Republic of Uzbekistan. As a result of the research, it was found that the payback period is 4 years and 3 years, respectively, in slightly and moderately saline soils. It has also been determined that desalination of highly saline lands is not beneficial and it is necessary to exclude them from agricultural use.